THE INFLUENCE OF PRIMARY SERVICE AND ISLAMIC BUSINESS ETHICS ON CUSTOMER RETENTION PT.BSI KCP SIPIROK ON EMPLOYEES - Ritonga, Kutbiah; Aminah, Rizka; Damar, Damar (Journal Of Sharia Banking, 2023)
There are still many K.H. Ahmad Dahlan Sipirok Islamic boarding school educators who do not use Islamic banks, they do not use Islamic banks because they do not know for sure the programs presented by these banks.  Thus, excellent service and Islamic business ethics can affect customer retention for employees of the K.H Ahmad Dahlan Sipirok Islamic boarding school.  The purpose of this study was to find out whether there is and how much influence excellent service and Islamic business ethics have on customer retention at Pondok Pesantren K.H.  Ahmad Dahlan Sipirok. The discussion in this study relates to marketing strategies in which it discusses excellent service, Islamic business ethics and customer retention.  The approach taken in business ethics is Islamically applied to Islamic banking as a strategy that can affect customer retention. This type of research is quantitative primary data research with a population of all educators and educational staff at Pondok Pesantren K.H.  Ahmad Dahlan Sipirok numbered 44 people. The sample in this study was 44 people who were determined using the saturation sampling technique.  The data analysis technique used to test the hypothesis is multiple linear regression analysis.  The analytical tool used to assist this research is SPSS version 23. The results of the research based on the results of data processing show that there is an influence of excellent service on customer retention at the K.H. Ahmad Dahlan sipirok Islamic boarding school and Islamic business ethics also influences customer retention at the K.H Ahmad Dahlan sipirok Islamic boarding school.  While the F test shows that there is an influence of excellent service and Islamic business ethics on customer retention.